Diversity management - Kirton, Gill (Henry Stewart Talks, 2011)
Reasons for emergence and evolution of diversity management, Differences between diversity management and equal opportunity, Outline of the business case, Four ways of theorising diversity, Dilemmas of diversity, Behind the business case, Problems for managers, Resistance and challenge